Seismic Shot Point Navigation Data from the Antarctic Peninsula acquired during R/V Maurice Ewing expedition EW9101 (1991) ... - Mutter, John; Austin, James; Shipley, Thomas; Dalziel, Ian (Interdisciplinary Earth Data Alliance (IEDA), 2008)
This data set was acquired with the LDEO Multi-Channel Seismic system during R/V Maurice Ewing expedition EW9101 conducted in 1991 (Chief Scientist: Dr. James Austin; Investigator: Dr. John Mutter). These data files are of ASCII format and include Seismic Shot Point Navigation data that provide the primary seismic navigation source for this cruise. Data were acquired as part of the projects: The Bransfield Strait-South Shetland Islands/Trench: Structural and Stratigraphic Evolution of a Linked(?) Back-arc/Fore-arc System and The Pacific Margin of the Antarctic Peninsula: A Marine Geophysical Study of the Tectonic Evolution of Andean-Type Orogens, and funding was provided by NSF grants: DPP89-17332 and OCE94-18135. ...